Respuesta :

Answer:

Step-by-step explanation:

I'm going to assume that you want  the value of x.

[(2x + 4) + 4]/(2x + 4) = [x + 7 +3)] / (x + 7)   Combine like terms on the numerator.

(2x + 8) / (2x + 4) = (x + 10) / (x + 7)                        Cross multiply

(2x + 8) (x + 7) = (2x + 4) (x + 10)                            Remove the brackets

2x^2 + 8x + 14x + 56 = 2x^2 + 20x + 4x + 40      Combine

2x^2 + 22x + 56 = 2x^2 + 24x + 40                      Subtract right from left

-2x +16 = 0                                                              16 from both sides

-2x = - 16                                                                 Divide by - 2

x = 8